MIND MAPPING TECHNIQUE TO ENHANCE JUNIOR HIGH STUDENT’S READING COMPREHENSION - Alviaderi Novianti; Novandy Adhitya; Yeli Welianty (English Education Department of STKIP Pasundan, 2020)
This research aimed at recognizing how mind mapping technique could enhance students’ reading comprehension. The investigation includes the teachers’ strategy in utilizing mind mapping techniques and the students respond to this technique. This research was carried out in one of tutorial course in Bandung. In gaining the research data, the writer gave a pre-test to the 6 students as research participant. Each student represented low, medium, and high achiever level. The data then collected through interview and observation. In its process, the research participants were required to read a text and then make their own mind map. At the end, the researcher conducted a post-test to know the significance. The post-test was in a form of questions related to the text read. In addition, the interview was also conducted to figure out the students’ learning experience. The data collected then assessed using High School Reading Comprehension Rubric. The assessment including the students’ ability in identifying the theme of the text and supporting details, summarizing the text, making inference, interpreting difficult vocabularies, and analyzing the purpose of the text. The result showed that there was significant different in students’ score before and after the treatment given. As well as on the positive responses showed by the students.